ISSR MARKER BASED DNA FINGERPRINTING IN RELEASED VARIETIES AND SELECTED SUPERIOR SOMACLONES OF GINGER (ZINGIBER OFFICINALE ROSC.) - PUJAITA GHOSH; M. R. SHYLAJA; P. A. NAZEEM (The Bioscan, 2014)
Inter Simple Sequence Repeats (ISSR) assay was performed to fingerprint ginger varieties released from Kerala Agricultural University, Vellanikkara, Keralaviz., “Athira”, “Karthika” and “Aswathi” and three selected superior somaclones of ginger viz., B3, 478R and 88R and source parent cultivars Maran and Rio-de-Janeiro. Good quality genomic DNA was extracted from ginger varieties/somaclones and source parent cultivars using CTAB method. Thirty ISSR primers were screened for amplification of genomic DNA and eleven primers were selected based on the amplification pattern. DNA fingerprints of the varieties/somaclones were developed utilizing the clear, distinct bands generated in ISSR profiles and size of the amplicons. Different colour codes were assigned for amplicons produced by the marker system in different varieties, somaclones and source parent cultivars to generate fingerprints. The fingerprints developed were unique and specific for the varieties/somaclones and source parent cultivars. The specific fingerprint data will serve as a mark for identifying the varieties/clones and could be utilized for registration and documentation of varieties, settling IPR issues and to avoid biopiracy.